Gender Inequality: Dampaknya terhadap Pendapatan Per Kapita (Studi Kasus 33 Provinsi di Indonesia 2011-2019) - Cita Puspita Sari (Jurnal Ekonomi Dan Statistik Indonesia, 2021)
Gender Inequality (gender inequality) is a classic problem in various countries, especially in developing countries like Indonesia. Gender inequality in various fields is considered to hinder economic growth. Slowing economic growth is considered to have a negative impact on income, both at the national level and the per capita level. Researchers are interested in examining per capita income as a proxy for economic growth. Per capita income is a measure of community welfare that is most often used by the government. This study aims to examine the description of gender inequality and per capita income in Indonesia, and analyze the impact of gender inequality on per capita income in Indonesia. The results of descriptive analysis show that there are still gender disparities in all provinces throughout Indonesia in 2011-2019. Furthermore, based on the results of the inference analysis using panel data, this study concludes that gender inequality simultaneously has a significant effect on per capita income. Gender inequality variables that have a partial effect include wages for women workers, women's labor force participation, and gender development